ANALISIS CAPITAL BUDGETING DALAM MENINGKATKAN KEPUTUSAN INVESTASI PADA PT. SAMUDERA INDONESIA - Heny Triastuti Kurnia Ningsih; Sonia Fara Diba (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
The research aims to analyze whether capital budgeting plays the role to improve investment decisions in the PT. Samudera Indonesia. The instrument used for data collection in this research is document of the company in spanning 2011-2016 and process of analyzing involves capital costs data. The results show that the effect of capital budgeting does not play the role to increase the value of the investment decision in 2014 and 2016, while in 2012, 2013 and 2015 value of DER is contributed to increase the investment decisions. Some factors that might influence the level of investment decisions are sales stability, asset structure, funding structure, profitability, taxes, controlling, management attitude, lender attitude, and rating appraisal agency, market condition, internal condition of company and financial flexibility.